OCCURRENCE OF ENTEROTOXIGENIC STAPHYLOCOCCI IN FROZEN FISHERY PRODUCTS - SANJEEV, S; IYER, K MAHADEVA; PANDURANGARAO, C C; JAMES, M ARUL (Fishery Technology, 2017)
Sixty six samples of frozen fishery product:; consisting of frozen crab meat, frozen prawns, frozen cuttle fish and frozen mussel collected from nine cold stoFes situated in and around Cochin city were examined for coagulase positive staphylococci. Forty eight samples (72.72%) revealed the presence of coagulase positive staphylococci, which were then tested for enterotoxigenity, employing cellophane-over-agar method forÂ· toxin production and optimum-sensitivity-plate (OSP) method for toxin detection. Seventy seven out of one hundred and two (75.49%) coagulase positive staphylococcal isolates from the above products produced enterotoxins A, B, C, D and E either singly or in combinations. Enterotoxin A and D were detected more often than others. The occurrence of enterotoxigenic staphylococci in frozen fishery product is reported for the first time in this country.